Societal determinants of violent death: The extent to which social, economic, and structural characteristics explain differences in violence across Australia, Canada, and the United States. (August 2019) - Wilkins, Natalie J.; Zhang, Xinjian; Mack, Karin A.; Clapperton, Angela J.; Macpherson, Alison; Sleet, David; Kresnow-Sedacca, Marcie-jo; Ballesteros, Michael F.; Newton, Donovan; Murdoch, James; Mackay, J. Morag; Berecki-Gisolf, Janneke; et al.
Abstract: In this ecological study, we attempt to quantify the extent to which differences in homicide and suicide death rates between three countries, and among states/provinces within those countries, may be explained by differences in their social, economic, and structural characteristics. We examine the relationship between state/province level measures of societal risk factors and state/province level rates of violent death (homicide and suicide) across Australia, Canada, and the United States. Census and mortality data from each of these three countries were used. Rates of societal level characteristics were assessed and included residential instability, self-employment, income inequality, gender economic inequity, economic stress, alcohol outlet density, and employment opportunities). Residential instability, self-employment, and income inequality were associated with rates of both homicide and suicide and gender economic inequity was associated with rates of suicide only. This study opens lines of inquiry around what contributes to the overall burden of violence-related injuries in societies and provides preliminary findings on potential societal characteristics that are associated with differences in injury and violence rates across populations. Highlights: This study opens lines of inquiry around what contributes to the overall burden of violence-related injuries in societies. Differences in homicide and suicide death between and within countries may be explained by social, economic, and structural characteristics. Residential instability, self-employment, and income inequality were associated with rates of both homicide and suicide. Gender economic inequity was associated with rates of suicide only.